Approaches of combining a 3D-printed elastic structure and a hydrogel to create models for plant-inspired actuators - Anil Bastola (MRS Advances, 2021)
Inspired by the interesting functional traits of a climbing cactus, Selenicereus setaceus, found in the forest formations of Southeastern Brazil, we formulated a hypothesis that we can directly learn from the plants to develop multi-functional artificial systems by means of a multi-disciplinary approach. In this context, our approach is to take advantage of 3D-printing techniques and shape-memory hydrogels synergistically to mimic the functional traits of the cactus. This work reports on the preliminary investigation of cactus-inspired artificial systems. First, we 3D-printed soft polymeric materials and characterized them, which defines the structure and is a passive component of a multi-material system. Second, different hydrogels were synthesized and characterized, which is an active component of a multi-material system. Finally, we investigated how the hydrogel can be integrated into the 3D-printed constructs to develop artificial functional systems.